A survey on students' perceptions on teachers' scaffolding in teaching writing for Science and Technology brief report / Adeline Gandhi David - David, Adeline Gandhi (2009)
This research is conducted to identify area of learning which students think is more significant to be highlighted when teachers scaffold writing instructions of brief reports, focusing on the first theme, 'Nature and Resources' only. It also attempts to identify type of scaffolding activity that students mostly preferred in everyday classroom of English for Science and Technology (EST) lessons and to examine its relevance in helping students to be independent writers. Form 4 EST students of SMK Tebakang are involved in this study. This study has implemented two instruments; a set of self-constructed questionnaires adapted from MacKenzie (1999) and semi-structured interviews. About 155 questionnaires are distributed to the respondents and only 152 are returned. Only 20 respondents are selected for the semi-structured interviews. Based on the findings of the study, the respondents believe that EST teachers should scaffold on language area when teaching writing because they claimed that if they are not proficient in English Language, they fail to understand the content knowledge and later have difficulty to convey ideas and justify opinions in writing form. Moreover, they claim they need to acquire certain and important language features when writing brief reports. Apart from that, they also believe that EST teachers should continue to scaffold acquisition of content knowledge. According to the respondents, if they are lack of the content knowledge, they will not be able to present information and to justify their ideas. Activity that the respondents claim to be effective when teachers scaffold writing instructions is group works. Furthermore, there are activities embedded in group works such as in class projects like preparing scrap book or pamphlets, group presentations, discussions like preparing drafts and completing worksheets. However, EST teachers need to be aware as students admitted that they were comfortable working in groups because they were able to switch to Bahasa Melayu. This will defeat the main objective of studying EST.